Photoreceptor protection: significance of docosanoids and elovanoids 2: bioactive derivatives of DHA - Bazan, Nicolas (Henry Stewart Talks, 2019)
AdipoR1 as an integral membrane protein, Neuroprotectin D1, Eicosanoids and docosanoids in neuroinflammation, Biosynthesis of elovanoids and expression of ELOVL4, Relationship between photoreceptor cells and retinal pigment epithelial cells